2018
DOI: 10.3390/molecules23092321
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Body Interactions in Molecular Docking Program Devised with Key Water Molecules in Protein Binding Sites

Abstract: Water molecules play an important role in modeling protein-ligand interactions. However, traditional molecular docking methods often ignore the impact of the water molecules by removing them without any analysis or keeping them as a static part of the proteins or the ligands. Hence, the accuracy of the docking simulations will inevitably be damaged. Here, we introduce a multi-body docking program which incorporates the fixed or the variable number of the key water molecules in protein-ligand docking simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…Among them, Triptolide was the only candidate active against 6LU7 protease in terms of hydrogen bonds. Further stability studies revealed that all of these successful ligands had a low binding energy and minimal RMSD values (1.01-2.79 Å), suggesting a stable adduct, in line with the reported studies (Ding et al, 2016;Xiao et al, 2018). The complete docking results are summarized in Table 1.…”
Section: 1screening Validation and Stability Analysissupporting
confidence: 82%
“…Among them, Triptolide was the only candidate active against 6LU7 protease in terms of hydrogen bonds. Further stability studies revealed that all of these successful ligands had a low binding energy and minimal RMSD values (1.01-2.79 Å), suggesting a stable adduct, in line with the reported studies (Ding et al, 2016;Xiao et al, 2018). The complete docking results are summarized in Table 1.…”
Section: 1screening Validation and Stability Analysissupporting
confidence: 82%
“…The closer the value to zero, the more similar the poses. RMSD value of less than 2Å is acceptable and suggests that the docking protocol used in this study has been carried out successfully (Xiao et al, 2018). The RMSD values of the poses were 1.040, 1.032, 1.310, and 1.930 Å in interactions with receptor TNF-α (PDB ID: 2AZ5), IL-1β ((PDB ID: 2NVH), IL-6 (PDB ID: 1ALU), and NF-κB p65 (PDB ID: 1OY3), respectively.…”
Section: Resultsmentioning
confidence: 89%
“…RMSD value is applied as a condition to evaluate the validity of the control docking process in which a control docking would be successful if RMSD obtained is no more than 2 Å. 19 Control docking result demonstrated that the RMSD value observed was 1.32 Å which means that the docking parameters set up were acceptable and therefore could be employed for virtual screening experiments upon compounds from B. javanica. The results (Table 1) showed that the free energy of binding of the compounds varies from -9.10 kcal/mol to -5.81 kcal/ mol.…”
Section: Discussionmentioning
confidence: 99%